Synthesis of Carbazole Alkaloids by Ring‐Closing Metathesis and Ring Rearrangement–Aromatization. Issue 52 (19th November 2015) - Dhara, Kalyan; Mandal, Tirtha; Das, Joydeb; Dash, Jyotirmayee
Abstract: Aprocess for the assembly of carbazole alkaloids has been developed on the basis of ring‐closing metathesis (RCM) and ringrearrangement–aromatization (RRA) as the key steps. This method is based on allyl Grignard addition to isatin derivatives to provide smooth access to 2, 2‐diallyl 3‐oxindole derivatives through a 1, 2‐allyl shift. The diallyl derivatives were used as RCM precursors to afford a novel class of spirocyclopentene‐3‐oxindole derivatives, which underwent a novel RRA reaction to afford carbazole derivatives. The synthetic sequence to carbazoles was shortened by combining the RCM and RRA steps in an orthogonal tandem catalytic process. The utility of this methodology was further demonstrated by the straightforward synthesis of carbazole alkaloids, including amukonal derivative, girinimbilol, heptaphylline, and bis(2‐hydroxy‐3‐methylcarbazole). Abstract : Just a hop, skip, and a jump away : The addition of allyl Grignard/indium reagents to isatins, ring‐closing metathesis (RCM), and ring rearrangement–aromatization (RRA) provided carbazole derivatives in high overall yield (see scheme). The RCM step afforded spirocyclic 3‐oxindoles, which underwent acid‐catalyzed RRA to give carbazoles. A step‐economical tandem RCM/RRA process was also developed and applied to the synthesis of carbazole alkaloids.